An Overview of Germanic Grisailles through the Stained-Glass Collection at Pena Palace - Rodrigues, Alexandra (2022)
The authors would like to thank António Nunes Pereira (Director) and all the team at Pena National Palace for in their efforts to make this and similar ongoing research possible through their collaboration and stimulus, as well as to Parques de Sintra—Monte da Lua for access to the collection studied. The authors also thank the anonymous reviewers for their valuable contribution to the improvement and enrichment of the manuscript. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.